THE INFLUENCE OF THYROTOXICOSIS ON THE MICROELEMENT COMPOSITION OF JAW BONES AND THE CHOICE OF ORTHOPEDIC DESIGN (International journal of artificial intelligence, 2026)
Thyrotoxicosis is a systemic endocrine disorder that significantly impacts bone tissue, including the jawbone. Microelement imbalances, decreased mineralization, and accelerated bone resorption complicate orthopedic treatment planning. This study aims to rationalize the choice of dental implant-supported orthopedic structures in patients with thyrotoxicosis. The study demonstrates the effectiveness of an orthopedically oriented, individualized approach based on a comprehensive assessment of bone quality and the use of digital technologies for planning the implant and orthopedic stages of treatment.